Flower orientation in Gloriosa superba (Colchicaceae) promotes cross-pollination via butterfly wings - Daniels, Ryan J (Ann Bot, 2020)
BACKGROUND AND AIMS: Complex modifications of angiosperm flowers often function for precise pollen placement on pollinators and to promote cross-pollination. We explore the functional significance of the unusually elaborate morphology of Gloriosa superba flowers, which are divided into one hermaphrodite meranthium and five male meranthia (functional pollination units of a single flower). METHODS: We used controlled pollination experiments, floral measurements, pollen load analyses and visitor observations in four populations of G. superba in South Africa to determine the breeding system, mechanism of pollination and role of flower in the promotion of cross-pollination. KEY RESULTS: We established that G. superba is self-compatible, but reliant on pollinators for seed production. Butterflies, in particular the pierid Eronia cleodora, were the primary pollinators (>90 % of visitors). Butterflies brush against the anthers and stigma during nectar feeding and pollen is carried on their ventral wing surfaces. Butterfly scales were positively correlated with the number of pollen grains on stigmas. We demonstrate that the styles were orientated towards clearings in the vegetation and we confirm that the highest proportion of initial visits was to hermaphrodite meranthia pointing towards clearings. CONCLUSIONS: The flower morphology of G. superba results in effective pollen transfer on the wings of butterfly visitors. The style-bearing hermaphrodite meranthium of the flowers orientates towards open spaces in the vegetation, thus increasing the probability that butterflies land first on the hermaphrodite meranthium. This novel aspect of flower orientation is interpreted as a mechanism that promotes cross-pollination.